Fix your period : six weeks to banish bloating, conquer cramps, manage moodiness, and ignite lasting hormone balance - Jardim, Nicole (Harper Wave, an imprint of HarperCollinsPublishers, 2020)
A life-changing, step-by-step, natural protocol to ignite lasting hormone balance and improve everything from PMS, period pain, and heavy periods to irregular cycles and missing periods, from Nicole Jardim, certified women's health coach and cohost of the podcast The Period Party.